Digital-Based Public Service Innovation On Taxpayer Compliance Through Taxpayer Satisfaction - Syahputra, Oky; Amril, Amril; Imam, Chairul; Mawarli, Mawarli; Ardilla, Yola (Yayasan Riset dan Pengembangan Intelektual, 2024)
The purpose of the study is to analyze the influence of the use of technology and modernization of the tax administration system on taxpayer compliance in increasing economic growth. This research method is quantitative research. The design of this study uses a cross-sectional design method with a sampling technique using purposive sampling. This study uses data analysis with the Partial Least Square (PLS) approach. Data were collected using questionnaires, literature studies, observations, interviews, Focus Group Discussions. The results of the study showed that digital-based Public Service Innovation has a significant effect on Taxpayer Satisfaction and Taxpayer Compliance. Taxpayer Satisfaction has an effect on Taxpayer Compliance.